2014
DOI: 10.1097/qai.0000000000000227
|View full text |Cite
|
Sign up to set email alerts
|

Weight as Predictors of Clinical Progression and Treatment Failure

Abstract: Objective To evaluate the value of time-updated weight and height in predicting clinical progression, immunological and virological failure in children receiving combination antiretroviral therapy (cART). Methods We used Cox regression to analyse data of a cohort of Asian children. Results 2608 children were included; median age at cART was 5.7 years. Time-updated weight for age Z score <−3 was associated with mortality (P < 0.001) independent of CD4%; and <−2 was associated with immunological failure (P ≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Wasting has been a significant complication of HIV infection since early in the epidemic [25,26], and remains an important clinical problem, particularly among children and adolescents living in Asian and African countries [27,28]. Although there are no studies demonstrating the adverse consequences of wasting on VR, it is well-documented that low weight-for-age has been significantly correlated with clinical and immunologic failure in children and adolescents [27,29]. Unfortunately, in our analysis, we did not include incident opportunistic infections (OIs).…”
Section: Discussionmentioning
confidence: 99%
“…Wasting has been a significant complication of HIV infection since early in the epidemic [25,26], and remains an important clinical problem, particularly among children and adolescents living in Asian and African countries [27,28]. Although there are no studies demonstrating the adverse consequences of wasting on VR, it is well-documented that low weight-for-age has been significantly correlated with clinical and immunologic failure in children and adolescents [27,29]. Unfortunately, in our analysis, we did not include incident opportunistic infections (OIs).…”
Section: Discussionmentioning
confidence: 99%
“…This could be because of the small number of children who were reported to have the conditions and most children had already been started on cotrimoxazole prophylactic therapy. However, several other studies have reported that these variables are associated with malnutrition in HIV infected patients [22, 26, 30]. Cotrimoxazole prophylactic therapy has been shown to improve their survival in children [31]; and improvement in anthropometric Z-scores among adults [32].…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition increases hospitalisation and mortality in HIV-infected children [ 43 45 ], but few associations with immunological failure exist [ 39 , 46 ] and none with virological failure on ART [ 39 , 47 ]. There further appears to be no literature about toxicity, other adverse effects, or the ART regimen of choice in severely malnourished children [ 48 ] and very few studies have assessed the effect of pharmacokinetics of ART specifically in malnourished children [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%